Analisis Pendaptan Usahatani Kubis (Brassica Oleracea L.) di Desa Tempok Kecamatan Tompaso Kabupaten Minahasa - Kolibu, Gabriela Triveina; Kapantow, Gene Henfried Meyer; Maweikere, Audrey Julia Maria (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This study aims to analyze the income of cabbage farming in Tempok Village, Tompaso District, Minahasa Regency. The research was conducted in Tempok Village, Tompaso District, Minahasa Regency, which is one of the places where most of the people live as farmers. Research activities were carried out from April to June in 2022. The data used in the study were primary data and secondary data. Primary data were obtained from direct interviews with farmers using a questionnaire. The number of respondents was 20 cabbage farmers who were randomly selected in 2 Jagas in Tempok Village, Tompaso District, Minahasa Regency. The sample is divided into two categories, namely farmers who have their own land and farmers who rent land. Based on the results of research on cabbage farming in Tempok Village, Tompaso District, Minahasa Regency, there are different. The amount of income received by farmers depends on the size of the land and the care of the cabbage plants owned by the farmers. The average income per hectare of cabbage farming in Tempok Village, Tompaso District for farmers who have their own land is Rp. 37,314,658, while the average income per hectare for farmers who rent land is Rp. 22,824,010.